The trend of Virtual Laboratory Apps: Ontology, Epistemology, and Axiology Perspectives to Support Contextualized Knowledge to Develop Learning Resource in Chemistry Education - eko yuliyanto; Siti Masitoh; Mochamad Nursalim (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
There were difficulties with the pandemic-related chemistry practicum learning. Therefore, a study of these issues is required. A virtual laboratory is one existing solution. This research seeks to identify the current Android VL trend. How does Android VL support chemistry education's scientific method? Do pupils now possess any new skills due to utilizing VL Android? This study is a case study. 237 Android Apps were found in the search results and categorized as Apps Virtual Laboratory (VL). The results of the selection produced 118 Apps. The study's findings indicate that chemical reactions are generally the focus of the VL, primarily created by the British state. It would be ideal to combine VL and lab practicum learning, as this would enable students to be better prepared for fieldwork in the real world and boost student self-efficacy and instructor teaching motivation.